Perubahan Mutu Ikan Gabus (Channa striata) Asap selama Penyimpanan - Hariyanto Sakti; Susi Lestari; Agus Supriadi (Jurnal FishtecH, 2016)
The purpose of this reseach was to determine quality changes of smoked snakehead (Channa striata) during storage with different smoked conditions. The methods of this research used experimental methods and the data was discussed as a descriptive to compare. The parameters observed were chemical analysis such as moisture content, water activity (aw), protein content, fat content and microbiologycal analysis of fungi. In the first storage of smoked snakehead fish has nutrient ingredient are moisture content 41.42%, protein content 42.23%, fat content 2.84%. In the end storage nutrient ingredient of smoked snakehead fish are moisture content 63.20%, protein content 27.64%, fat content1.79%. Smoked snakehead fish was saved at normal temperature for 7 days has water activity and total of fungi colony smoked snakehead fish was save for 7 days is 2.409 x 102, but the fungi was not growth in the first storage.